1996
DOI: 10.1097/00006123-199612000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Use of Methylprednisolone as an Adjunct in the Management of Patients with Penetrating Spinal Cord Injury: Outcome Analysis

Abstract: The administration of methylprednisolone did not significantly improve functional outcomes in patients with gunshot wound injuries to the spine or increase the number of complications experienced by patients during their hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(54 citation statements)
references
References 10 publications
0
48
1
5
Order By: Relevance
“…Complete deficit was reported to be more dependent on spinal injury level, violation of bone architecture by the bullet, and presence of a bullet in the canal. Based on data from 10 studies, CGSWSCI rate at the cervical level was 30% (315 of 1055), at the thoracic level was 49% (518 of 1055), and at the lumbosacral level was 21% (222 of 1055) [13,[17][18][19][20][21][22][23][24][25]. Of the cervical SCIs, two studies examining gunshot injuries to the cervical spine reported the rate of complete injury to be approximately 70% (46 of 66) [26,27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete deficit was reported to be more dependent on spinal injury level, violation of bone architecture by the bullet, and presence of a bullet in the canal. Based on data from 10 studies, CGSWSCI rate at the cervical level was 30% (315 of 1055), at the thoracic level was 49% (518 of 1055), and at the lumbosacral level was 21% (222 of 1055) [13,[17][18][19][20][21][22][23][24][25]. Of the cervical SCIs, two studies examining gunshot injuries to the cervical spine reported the rate of complete injury to be approximately 70% (46 of 66) [26,27].…”
Section: Resultsmentioning
confidence: 99%
“…Steroid administration was documented in four studies, three of which reported the association with neurological recovery [18,20,23]. Overall, no major clinical benefit was demonstrated with steroid administration.…”
Section: Resultsmentioning
confidence: 99%
“…There is also no role for the administration of trauma-dose Solu-Medrol in these patients. 26 The only absolute indications for surgery are to repair a CSF-cutaneous/pleural fistula or if the patient has progressive neurological decline correlated with compression of neural elements on imaging studies.…”
Section: Our Recommendations For Deployed Military Neurosurgeonsmentioning
confidence: 99%
“…50,51 Administration of methylprednisolone had a high incidence of pancreatitis, while dexamethasone had the highest GIT complication rate. 51 Heiden et al reported that the outcome and potential for recovery depended on the initial injury, and that surgical intervention did not alter neurological outcome, in either complete or incomplete patients.…”
Section: Neurological Injurymentioning
confidence: 99%